2013
DOI: 10.7554/elife.01519
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of chiral proofreading during translation of the genetic code

Abstract: The biological macromolecular world is homochiral and effective enforcement and perpetuation of this homochirality is essential for cell survival. In this study, we present the mechanistic basis of a configuration-specific enzyme that selectively removes D-amino acids erroneously coupled to tRNAs. The crystal structure of dimeric D-aminoacyl-tRNA deacylase (DTD) from Plasmodium falciparum in complex with a substrate-mimicking analog shows how it uses an invariant ‘cross-subunit’ Gly-cisPro dipeptide to capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 44 publications
2
79
1
Order By: Relevance
“…Both the Bacterial (Ec) and Eukaryotic (At) DTD1s did not act on NELATs and also on NEDATs (Fig: 2C, 2D) (Extended Data Fig: 5). DTD1's lack of activity on NEDATs is further corroborated by the earlier crystal structure of DTD1 in complex with substrate analog D-Tyr3AA 6,15 . Wherein the D-amino acid of D-aminoacyl-tRNA snugly fits into the active site of DTD1, thereby sterically excludes N-ethylated amino group of D-amino acid ( Fig: 2E).…”
Section: Dtd2 Alleviates Anaerobic Stress In Plants By Recycling Nedatssupporting
confidence: 54%
See 1 more Smart Citation
“…Both the Bacterial (Ec) and Eukaryotic (At) DTD1s did not act on NELATs and also on NEDATs (Fig: 2C, 2D) (Extended Data Fig: 5). DTD1's lack of activity on NEDATs is further corroborated by the earlier crystal structure of DTD1 in complex with substrate analog D-Tyr3AA 6,15 . Wherein the D-amino acid of D-aminoacyl-tRNA snugly fits into the active site of DTD1, thereby sterically excludes N-ethylated amino group of D-amino acid ( Fig: 2E).…”
Section: Dtd2 Alleviates Anaerobic Stress In Plants By Recycling Nedatssupporting
confidence: 54%
“…Apart from plants, DTD2 is also conserved in Archaea ( We next interrogated substrate specificity of DTD2 in terms of modification by performing deacylations with N-acetyl-D-aa-tRNAs and found that both, archaeal (Pho) and plant (At) DTD2s did not hydrolyse acetyl substrates (Fig: 3G, H) suggesting, DTD2 is specific for ethyl modification and evolved exclusively for ND activity. It is therefore intriguing to probe 6 what physiological constraints necessitated the conservation of DTD2 and its ND activity in Archaea and plants. To this end, we searched for common physiological and biochemical characteristics among Archaea and plants.…”
Section: Nd Activity Is Rooted In the Archaeamentioning
confidence: 99%
“…The other PDB entries with less sequence similarity or coverage, listed in Table S2, are oxidoreductases, (5ID2, 3DRN), deacylases (1J7G, 2DBO, 1JKE, 3KNP, 3KO3, 3KO4, 4NBJ, 4NBI, 5J61), a PH domain of Evectin‐2 (2DHI) and an oligomerization domain of Dmp53 (2RP4). The structural and sequential coverage of these proteins with a known structure and function is not high enough to make a reliable assumption of the possible cellular function of HVO_2922 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The genes encoding E. coli DTD and Thermus thermophilus EF-Tu, and cDNA encoding M. musculus (residues 1-147) were cloned (with C-terminal 6X His-tag), expressed and purified as mentioned in Ahmad et al, 2013 and Kuncha et al, 2018. Briefly the proteins were overexpressed in E. coli BL21(DE3) by growing the culture to 0.6 OD (600 nM) at 37°C, followed by induction using 0.5 mM IPTG for 12 hours at 18°C.…”
Section: Methodsmentioning
confidence: 99%